P105 Identification of rare coding variants in IL-1-related pathways in patients with adult-onset still's disease. (March 2019) - Cavalli, G; van Deuren, R; Arts, P; Steehouwer, M; Sfriso, P; Colafrancesco, S; Priori, R; Cantarini, L; Baldissera, E; van de Veerdonk, F; Dagna, L; Hoischen, A; et al.
Abstract : Career situation of first and presenting author: Assistant. Introduction: Adult-onset Still's disease (AOSD) is a rare autoinflammatory disease characterized by fever, arthritis, and multi-organ involvement. Inflammation in AOSD is mediated by interleukin (IL)-1β, as confirmed by the clinical efficacy of selective blockers. The genetic predisposition to this IL-1-driven inflammation remains nevertheless elusive. Previous studies failed to identify associations between polymorphisms in the IL-1 genes and AOSD, thus pointing at more complex genetic mechanisms. These cannot be investigated with traditional techniques for genetic partitioning, such as GWAS, which only assess common variants and polymorphisms. Studies focusing on highly penetrant rare variants or different types of mutations (i.e. small copy-number variations; insertions/deletions) are warranted. Objectives: We hypothesized that genetically determined changes in IL-1-related pathways resulting in excessive IL-1β activity lead to the development of autoinflammation in AOSD. Scope of this study was to unravel the combined mutational variation of a network of IL-1-related receptors, pathways, counter-regulators, and cellular processes possibly involved in the pathogenesis of IL-1-mediated inflammation. Methods: We collected clinical and genetic data from a large cohort of 76 AOSD patients and developed an innovative platform based on molecular inversion probes technology, which enables highly multiplexed targeted-resequencing of the coding sequence of 48 genes related to the IL-1-pathway, and allows studying rare and common variants in one assay. We have also screened 500 healthy controls, and 1000s of samples with other disorders using the same assay. Results: We identified rare and unique (i.e. private variants) in the IL-1 pathway in several individuals with AOSD. Whether any of these are involved in a strong predisposition to AOSD is currently followed-up. Rare genetic variants have been identified in six IL-1-pathway 'clusters': Inflammasomes; IL–1 pathway; IL–1 family; IL–18 pathway; Autophagy; ROS production. Conclusions: Unraveling the genetic bases of inflammation in AOSD deepens our understanding of the human innate immunome. This study platform may now serve for the genetic analysis of other IL-1-mediated conditions (i.e. gout and other autoinflammatory diseases), whose genetic predisposition remains elusive. Equally important, the identification of pathways amenable to targeting with small molecules or biologics may translate into remarkable clinical implications. Disclosure of Interest: None declared.